Zakat Distribution Concentration on Poverty Alleviation: A Spatial Analysis in Indonesia-Malaysia Using LQ-DLQ and Panel Data Models - Haq, Muhammad Syakhsan (International Journal of Zakat, 2025)
Zakat has a strategic role in reducing poverty, but its effectiveness depends on the concentration of distribution in each region. This study maps the spread of zakat distribution concentration in Indonesia and Malaysia using the modified Location Quotient and Dynamic Location Quotient (LQ-DLQ) method for spatial analysis and measures its impact on poverty through panel data regression models. This approach also compares the effectiveness of the voluntary zakat system in Indonesia with the mandatory zakat system in Malaysia. The results show that the concentration of zakat distribution significantly reduces poverty. Moreover, interaction analysis shows that the mandatory zakat system in Malaysia is more effective in reducing poverty than the voluntary zakat system in Indonesia. Other results also found areas with superior zakat distribution concentration such as DKI Jakarta, Selangor, and Kelantan, but there are also areas such as East Java which although has an average zakat distribution above the national average, the concentration is still classified as underdeveloped. This research recommends amil to optimize zakat distribution locally, especially in underdeveloped areas, and encourage collaboration between countries to improve zakat management.